Citizens' preferences for inter-municipal cooperation in rural areas: Evidence from a survey in three Hessian counties - Christian Bergholz; Ivo Bischoff (Philipps-University Marburg, School of Business and Economics, 2015)
In rural areas, small and medium-sized municipalities are challenged by demographic change and intensified competition for capital and high-skilled labor. Inter-municipal cooperation (IMC) is often regarded as a significant element of a strategy to meet these challenges. Based on a survey in three rural counties in the German state of Hesse, we present first evidence on citizens' policy preferences regarding IMC. Policy preferences are found to be driven primarily by individual characteristics. The strongest factor reducing citizens' support is the belief that IMC reduces citizens' influence and control. Support is higher among citizens who assess the current service quality as low and/or assess the future perspective of their home municipality as negative. Trust in local politicians and a high degree of emotional attachment to the home municipality have a negative impact on subjects' support for IMC. None of the municipal characteristics like municipal size or fiscal stress, nor the availability of suitable partner municipalities are found to drive citizens' preferences.
Keywords: H77; D72; 330; fiscal federalism; inter-municipal cooperation; voter preferences; survey; Germany